MAIN AMENDMENTS AND ADDENDUMS INTRODUCED TO THE NEW EDITION OF THE CONSTITUTION OF THE NEW UZBEKISTAN - Abdunazarov Behzod (Western European Studies, 2024)
This article is devoted to the most important changes made to the Constitution of the Republic of Uzbekistan and their significance according to the constitutional law "On the Constitution of the Republic of Uzbekistan" adopted in the referendum on April 30.
Keywords: New Uzbekistan; referendum; state